Improved first-pass spiral myocardial perfusion imaging with variable density trajectories - Salerno, Michael; Sica, Christopher; Kramer, Christopher M.; Meyer, Craig H. (Magnetic resonance in medicine, 2013)
Purpose To develop and evaluate variable‐density spiral first‐pass perfusion pulse sequences for improved efficiency and off‐resonance performance and to demonstrate the utility of an apodizing density compensation function (DCF) to improve signal‐to‐noise ratio (SNR) and reduce dark‐rim artifact caused by cardiac motion and Gibbs Ringing. Methods Three variable density spiral trajectories were designed, simulated, and evaluated in 18 normal subjects, and in eight patients with cardiac pathology on a 1.5T scanner. Results By using a DCF, which intentionally apodizes the k‐space data, the sidelobe amplitude of the theoretical point spread function (PSF) is reduced by 68%, with only a 13% increase in the full‐width at half‐maximum of the main‐lobe when compared with the same data corrected with a conventional variable‐density DCF, and has an 8% higher resolution than a uniform density spiral with the same number of interleaves and readout duration. Furthermore, this strategy results in a greater than 60% increase in measured SNR when compared with the same variable‐density spiral data corrected with a conventional DCF (P < 0.01). Perfusion defects could be clearly visualized with minimal off‐resonance and dark‐rim artifacts. Conclusion Variable‐density spiral pulse sequences using an apodized DCF produce high‐quality first‐pass perfusion images with minimal dark‐rim and off‐resonance artifacts, high SNR and contrast‐to‐noise ratio, and good delineation of resting perfusion abnormalities. Magn Reson Med 70:1369–1379, 2013. © 2012 Wiley Periodicals, Inc.